KESEJAHTERAAN KARYAWAN TETAP TERHADAP KONTINUITAS USAHA TAMBAK UDANG, STUDI KASUS TAMBAK UDANG CV KARUNIA DEWATA KARANGASEM BALI - Dimas Wahyu Setyawan; Tony Antonio; Agoes Tinus Lis Indrianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to explore the relationship between permanent employee welfare and business continuity in the shrimp farming industry, using a case study of CV Karunia Dewata in Karangasem, Bali. A qualitative case study approach was employed, utilizing in-depth interviews and participatory observations as the primary data collection methods. The results indicate that employee welfare—including physical, mental, social, and economic aspects—significantly affects work productivity, loyalty, and discipline. The lack of attention to employee welfare was identified as a key factor contributing to non-compliance with SOPs, which negatively impacted biosecurity and production output. These findings underscore the strategic role of employee welfare in maintaining workforce stability and operational continuity. The study also offers practical recommendations to enhance welfare policies and adaptive supervision systems to ensure long-term sustainability of shrimp farming businesses.